Recent developments in intelligent nature-inspired computing - Patnaik, Srikanta (Advances in computational intelligence and robotics (ACIR) book series, 2017)
"[This book] is an authoritative reference source for the latest scholarly material on natural computation methods and applications in diverse fields. Highlighting multidisciplinary studies on swarm intelligence, global optimization, and group technology, this publication is an ideal reference source for professionals, researchers, scholars, and engineers interested in the latest developments in computer science methodologies" - Provided by publisher